The use of storytelling methods by teachers and their effects on children’s understanding and attention span - Bartan, Murat (Southeast Asia Early Childhood Journal, 2020)
This research was carried out to determine the effect of different storytelling methods on children’s understanding and attention span of pre-school education period. The research is a quantitative study that took place in two stages. In the first stage, with the descriptive screening model, it was determined which of the different storytelling methods used by a total of 72 preschool teachers during the education period. In the second stage, the effectiveness of the four different storytelling methods that teachers stated most was examined by using comparative non-synchronized post-test design. The experimental stage was carried out with 40 children, whose ages ranging from five to six, receiving pre-school education. In the research, each of the four separate stories was presented with four different storytelling methods. As a result of the research, it was determined that the method of telling the story most frequently used by the teachers was “By reading from the story-tale book”, and the method they used the least was the telling with the “Shadow puppet”. When looking at the level of children’s understanding of stories, it was determined that the most effective method was the method of telling “By reading from the story-tale book”, and the least effective method was the method of telling with the “Story card”. When the effects of the stories on the focus and attention span of the children were analysed, it was determined that the most effective method was the method of “Storytelling using the computer”, and the least effective method was the method of storytelling with the story card. At the end of this research, it was concluded that the effective use of audio-visual elements in storytelling methods was the most effective factor for children to understand the story and focus on it for a long time.